The Profile Of Native Chicken Farm At Nagari Sinyamu, Tanjung Gadang District, Sijunjung Regency - Hera Dwi Triani; Maiyontoni Maiyontoni; Elmira Yanti (Department of Agriculture, 2022)
Nagari Sinyamu is one of the villages in the Tanjung Gadang sub-district, Sijunjung district, most of the people are farmers. Free-range chicken is a potential family side business to be developed, where the source of agricultural waste feed is quite available. This is a supporting factor for the development of native chickens. The purpose of this study was to determine the profile of native chickens in Nagari Sinyamu. This research method uses a survey method by collecting primary data and secondary data. This research material uses books, camera pens and questionnaires. The data obtained are arranged in tabulated form (percentages and numbers) and sentence statements, the results of data processing are analyzed descriptively, qualitatively, and quantitatively. Based on the research, the number of respondent chicken breeders in Nagari Sinyamu was 40 families with a total population of 633 individuals. The characteristics of the chicken respondent breeders in Nagari Sinyamu are post-productive average 52.5%), the sexes of men and women are the same (50%). The level of education in general is SD Equivalent (72.5%), with experience raising for more than 10 years (50%) and the scale of the free-range chicken business in Nagari Sinyamu is only a side business (100%) with an extensive rearing system (77.5 %). In the management of raising native chickens in Nagari Sinyamu, the seeds used are local seeds (100%), the feed given is not according to the standard of livestock nutrition needs (100%) and there is no treatment or prevention of disease (90%) but sick chickens have been treated. separated and marketing of free-range chicken in Nagari Sinyamu is generally for needs and sold to the surrounding community if they need money (62.5%). Based on the results of the study, it can be concluded that the profile of free-range chicken farms in Nagari Sinyamu, Tanjung Gadang sub-district, Sijunjung district is a side business on a micro scale.